2015
DOI: 10.1111/ejn.13036
|View full text |Cite
|
Sign up to set email alerts
|

Functional lateralization of temporoparietal junction – imitation inhibition, visual perspective‐taking and theory of mind

Abstract: Although neuroimaging studies have consistently identified the temporoparietal junction (TPJ) as a key brain region involved in social cognition, the literature is far from consistent with respect to lateralization of function. For example, during theory‐of‐mind tasks bilateral TPJ activation is found in some studies but only right hemisphere activation in others. Visual perspective‐taking and imitation inhibition, which have been argued to recruit the same socio‐cognitive processes as theory of mind, are asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
108
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(130 citation statements)
references
References 47 publications
(71 reference statements)
15
108
6
1
Order By: Relevance
“…Thus, anodal tDCS was applied to the right TPJ or IFC in the current study. The stimulation sites for the IFC and TPJ were FC6 (Holland et al, 2011; Hogeveen et al, 2015) and CP6 (Santiesteban et al, 2012a, 2015; Hogeveen et al, 2015), respectively. The reference electrode was placed horizontally over the vertex, individually measured, and then the vertex at 50% of the distance between the preauricular points, crossing a point 50% of the distance between the inion and nasion, was marked.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, anodal tDCS was applied to the right TPJ or IFC in the current study. The stimulation sites for the IFC and TPJ were FC6 (Holland et al, 2011; Hogeveen et al, 2015) and CP6 (Santiesteban et al, 2012a, 2015; Hogeveen et al, 2015), respectively. The reference electrode was placed horizontally over the vertex, individually measured, and then the vertex at 50% of the distance between the preauricular points, crossing a point 50% of the distance between the inion and nasion, was marked.…”
Section: Methodsmentioning
confidence: 99%
“…However, there was an increase in face touching (imitation) during a social interaction task in the individuals who received anodal tDCS to the right IFC. Santiesteban et al (2015) performed anodal tDCS on the right or left TPJ and reported a significant decrease in the interference effect of the inhibition of imitation, regardless of whether the right or left TPJ was stimulated. They also reported that accuracy during the visual perspective-taking task increased significantly, regardless of the side of the TPJ that was stimulated.…”
Section: Introductionmentioning
confidence: 99%
“…Brain stimulation techniques have confirmed that ToM could be considered a multidimensional construct, and that different brain regions are differentially recruited during cognitive and affective ToM tasks21222324. To the best of our knowledge, to date, only two studies applied brain stimulation to investigate gender differences in the social cognitive domain2526.…”
mentioning
confidence: 99%
“…Additional adjacent areas may participate in animacy attribution. The temporoparietal junction, particularly on the left, is heavily involved in the ability to take the visual perspective of others (Santiesteban, Banissy, Catmur, & Bird, 2015; Schurz, Aichhorn, Martin, & Perner, 2013). Two other adjacent areas not shown in this study but previously implicated for animacy detection, the posterior superior temporal sulcus (pSTS) and the fusiform gyrus (FG) (Gao et al, 2012; Hillebrandt, Friston, & Blakemore, 2014; Lee et al, 2014; Schultz, Friston, O’Doherty, Wolpert, & Frith, 2005; Shultz, van den Honert, Engell, & McCarthy, 2015; Shultz & McCarthy, 2014), are involved in biological motion detection and mostly likely part of the agency complex (Castelli et al, 2000; Gobbini et al, 2011; Grèzes et al, 2001).…”
Section: Discussionmentioning
confidence: 99%